COVID-19 Shows the Need to Make Church More Flexible - Pillay, Jerry (Transformation, 2020)
The COVID-19 challenge is unprecedented. It has caused enormous trauma, disrupted economies, social life, mass transportation, work and employment, supply chains, leisure, sport, international relations, academic programmes; literally everything. Churches and religious communities have not been spared; they have been severely affected and, in all likelihood, permanently transformed by the pandemic. The pre-COVID-19 world is gone, replaced by a ‘new normal’. The new landscape calls for both resilience and adaptation, embracing new ways of doing things and of being church. Churches have to adapt; they have to ask themselves questions about the implications for being church in this ‘new normal’ context. This article aims to explore the impact of the coronavirus on the mission and theology of the church.